1983
DOI: 10.1080/14640748308400893
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Partial Reinforcement on Serial Autoshaping with Pigeons

Abstract: The effect of partial reinforcement on the rate of responding during the first element of a serial compound was investigated using autoshaping in pigeons. Experiment I employed the illumination of a response key by two different colours as the elements of the compound. Responding during the first element was faster when this stimulus was intermittently paired with the second element and the unconditioned stimulus than when a continuous reinforcement schedule was employed. Experiment II demonstrated that this e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
34
0
1

Year Published

1987
1987
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 16 publications
6
34
0
1
Order By: Relevance
“…It may be that choice proportions reflect the joint contribution of the lower rate of primary reinforcement and the higher value of the 50% food terminal link, whereas rate of responding during the terminal links leading to food reflects only the latter. Dunn and Spetch (1990) and Spetch et al (1990) noted that results from the percentage reinforcement procedure were analogous to findings from serial autoshaping studies, in which responding to a stimulus that had an intermittent relationship to the occurrence of a stimulus associated with food was higher than responding to a stimulus that was always followed by a stimulus associated with food (Collins & Pearce, 1985;Collins, Young, Davies, & Pearce, 1983). However, Pearce and Collins (1987) used choice probes to test preference between stimuli that were intermittently or perfectly predictive of a stimulus associated with food, and found that their measures of preference did not mirror the difference in response rates found in serial autoshaping.…”
Section: Discussionmentioning
confidence: 55%
“…It may be that choice proportions reflect the joint contribution of the lower rate of primary reinforcement and the higher value of the 50% food terminal link, whereas rate of responding during the terminal links leading to food reflects only the latter. Dunn and Spetch (1990) and Spetch et al (1990) noted that results from the percentage reinforcement procedure were analogous to findings from serial autoshaping studies, in which responding to a stimulus that had an intermittent relationship to the occurrence of a stimulus associated with food was higher than responding to a stimulus that was always followed by a stimulus associated with food (Collins & Pearce, 1985;Collins, Young, Davies, & Pearce, 1983). However, Pearce and Collins (1987) used choice probes to test preference between stimuli that were intermittently or perfectly predictive of a stimulus associated with food, and found that their measures of preference did not mirror the difference in response rates found in serial autoshaping.…”
Section: Discussionmentioning
confidence: 55%
“…Thus, on reinforced trials the US would have been similarly processed in both conditions. Note too that the high level of US expectancy in the PRF condition would tend to maximize the surprise effect of the omission of the US on nonreinforced trials in the PRF condition, increasing the chance of enhancement of processing of the CS on those trials, as was intended in Experiment 3 and as was observed by Pearce and his colleagues Collins et al, 1983).…”
Section: Discussionmentioning
confidence: 86%
“…Thus, the associability of a CS should be maintained at a higher value with partial reinforcement procedures than with consistent reinforcement procedures. Using orienting responses as an indicator of associability, Pearce and colleagues (e.g., Collins, Young, Davies, & Pearce, 1983;Kaye & Pearce, 1984;Pearce, Kaye, & Collins, 1985) found substantially greater associability of CS trained with a variety of partial reinforcement procedures than of that trained with consistent reinforcement procedures.…”
Section: Methodsmentioning
confidence: 99%
“…One interpretation of this latter finding is that the rats allocated less attention to the PRF cues than to the CRF cues within the 5-cue array and hence performance to PRF cues was more disrupted by the further demands placed on attentional processing by shortening their duration. Thus, unlike in tasks that assess the acquisition of new learning (e.g., Collins & Pearce, 1985;Collins et al, 1983, Kaye & Pearce, 1984, partially-reinforced cues control less attention than consistently-reinforced in the task studied here.…”
Section: Discussionmentioning
confidence: 92%
“…Next, we assessed the effects of a cue duration challenge, in which the duration of the cues was reduced first to 250 ms and then to 100 ms. If PRF cues control more attention than CRF cues in this task, as they do in tasks that measure rates of new learning about cues (Collins & Pearce, 1985;Collins et al, 1983;Kaye & Pearce, 1984), then responding to the PRF cues should be less susceptible to the cue-duration challenge. By contrast, if rats devote fewer attentional resources to PRF cues than to CRF cues, then responding to PRF cues should be more susceptible to that challenge.…”
Section: Methodsmentioning
confidence: 99%